RANCANG BANGUN AKSES RUANGAN MENGGUNAKAN SISTEM PENGENALAN WAJAH - Rawing, Rawing; Satriyo, Satriyo (entries, 2024)
In modern times filled with technological advances, concerns about crime, especially the rise of theft cases, are increasing. Various methods are used by criminals to open the door of the house due to weaknesses in traditional security systems, such as door locks or padlocks. Therefore, a more sophisticated security solution is needed to protect the room in one way, namely the use of an automatic door security system with facial recognition as an exclusive method to grant access.Facial recognition as a biometric technology is considered an innovative solution in protecting access to rooms. The face recognition process involves face detection, feature extraction, and face recognition, forming a system that can accurately identify individuals. By using a camera as a sensor, users do not need to make physical contact, simply facing the camera to prove their identity. The main advantage of this system is its ability to reduce the risk of crime, as the room door will only open if the detected face has been registered in the system.This research has successfully built a reliable face recognition system for automatic doors by using Huskylens camera as a sensor, Solenoid as a door lock, and ESP32 as a microcontroller, this tool is expected to be an effective solution to improve room security. The main objective of the researcher is to successfully implement a facial recognition system that is accurate and provides proper access to entitled individuals, creating an additional layer of security without reliance on traditional physical locks.Keywords: Face Recognition, ESP32.